Targeted Next-Generation Sequencing Identified Novel Compound Heterozygous Variants in the PTPRQ Gene Causing Autosomal Recessive Hearing Loss in a Chinese Family - Jin, Yuan; Liu, Xiao-Zhou; Xie, Le; Xie, Wen; Chen, Sen; Sun, Yu (Frontiers in Genetics, 2022)
Hearing loss is among the most common congenital sensory impairments. Genetic causes account for more than 50% cases of congenital hearing loss. PTPRQ gene, encoding protein tyrosine phosphatase receptor Q, plays an important role in maintaining the stereocilia structure and function of hair cells. Mutations in the PTPRQ gene have been reported to cause hereditary sensorineural hearing loss. By using next-generation sequencing and Sanger sequencing, we identified a novel compound heterozygous mutation (c. 997 G > A and c. 6603-3 T > G) of PTPRQ in a chinese consanguineous family. This is the first report linking these two mutations to recessive hereditary sensorineural hearing loss. These findings contribute to understand the relationship between genotype and hearing phenotype of PTPRQ-related hearing loss, which may be helpful to the clinical management and genetic counselling.